An investigation of significant architectural settings of a Malacca traditional mosque: a case study of Tengkera mosque / Maheran Yaman, Nur Fadhilah Rozali and Fadzidah Abdullah - Yaman, Maheran; Rozali, Nur Fadhilah; Abdullah, Fadzidah (UiTM Press, 2023)
Throughout Islamic history, the mosque has been known as a house of worship, a centre of community gatherings, meetings, and learning. In Southeast Asia, the traditional mosque's design started receiving the blended culture of Javanese, Chinese, and Malay design influences from various communities. Each mosque's significant design and beauty lie in the invention's form, ornamentation, and decorations. Traditional mosques in Malaysia are believed to be constructed initially around 1300-1800, and some of them are still standing now. However, some historical and heritage mosques are not recognised due to degradation or demolition and lack of promotion by the authorities, resulting in tourists only experiencing the tangible heritage portrayed in the mosque's façade and style. Other than that, the limited resources, such as the historical background of the mosque and its characteristics, need to be studied and revealed to the tourists, as it can engage tourists' experience in the historical sites and provide interactive learning purposes to tourists. Learning new cultures, engaging in new experiences, and community involvement could enhance tourists' motivation during travel. Subsequently, the study focuses on one of the oldest traditional mosques in Malacca, Tengkera Mosque, as a tourism destination. This study used the qualitative method, the literature review and the structured observation to investigate and identify the significant exterior and interior components of the mosque, including the formative aesthetics, materials, and decorative features, to gain detailed information on the characteristics of the mosque. The main findings of the case study revealed the external components of the mosque (roof form, tower, and archway) and internal components (layout plan, prayer hall, mihrab, minbar) showcases a remarkable multi-cultural influence of Javanese, Chinese, and local portrayed at the mosque's façade design. Moreover, the material aspects of the mosque also showed a combination of foreign materials like main pillars originating from the Kalimantan, Indonesia, and tiles from China. The case study's findings will benefit the locals and tourism industry by better understanding of historical and cultural heritage buildings and creating tourists' engagement with the cultural values of Malacca, a historical city.